Mitochondrial transfer in the HSC–HCC–macrophage network shapes hepatocellular carcinoma progression - La Zhang; Cong Ren; Miao He; Xinyu Chen; Hongqing Liu; Yilin Liu; Jing Luo; Zhenghang Li; Jianwei Wang; Wenjun Miao; Qiling Peng; Ning Jiang (Proceedings of the National Academy of Sciences, 2026)
Mitochondrial crosstalk between tumor cells and components of the tumor microenvironment (TME) is a critical yet underexplored mechanism driving hepatocellular carcinoma (HCC) progression. Here, we demonstrate that in HCC, mitochondria can be transferred from hepatic stellate cells to cancer cells via tunneling nanotubes (TNTs), supplying essential energy for tumor growth. Simultaneously, cancer cells offload damaged mitochondria to macrophages through extracellular vesicles (EVs), facilitating their clearance and promoting tumor development. To disrupt this mitochondrial exchange, we developed a responsive liposomal nanocarrier (L&G@Lipo PPV ) coencapsulating L-778123 and GW4869 to simultaneously inhibit TNT-mediated and vesicle-mediated mitochondrial transfer. This work provides the first comprehensive evidence of mitochondrial transfer dynamics in the TME, with tumor cells as the central hub, and highlights L&G@Lipo PPV as an innovative and effective strategy to block mitochondrial crosstalk. Our findings address critical challenges of drug solubility and delivery, offering a rational approach to reprogram the TME and suppress liver cancer progression.